2020
DOI: 10.1177/1558925020916458
|View full text |Cite
|
Sign up to set email alerts
|

Study on the NCO index and base knitted fabric substrates on the thermal, chemical, and mechanical properties of solvent-less formulations polyurethane artificial leather

Abstract: In this article, we have studied the thermal, chemical, and mechanical properties of the polyurethane artificial leather. Polyurethane artificial leathers were made from polyol, diisocyanate, chain extender, a catalyst, polyester circular knitted fabric, and warp knitted fabric. After manufacturing the artificial leathers, the properties of six different samples were investigated according to the NCO index. The equivalence ratios of the isocyanates to polyols containing a hydroxyl group are referred to as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…PU materials can be successfully synthesized into artificial leather materials after weaving and knitting by different weaving mode in figure 2. Eun et al [10] prepared and do a research on the thermal, chemical and mechanical properties of PU artificial leather with different NCO index ratios. The results showed that with the increase of NCO index, the functional groups and crosslinking degree of unreacted NCO increased.…”
Section: Application Of Functional Polyurethane In Artificial Leathermentioning
confidence: 99%
“…PU materials can be successfully synthesized into artificial leather materials after weaving and knitting by different weaving mode in figure 2. Eun et al [10] prepared and do a research on the thermal, chemical and mechanical properties of PU artificial leather with different NCO index ratios. The results showed that with the increase of NCO index, the functional groups and crosslinking degree of unreacted NCO increased.…”
Section: Application Of Functional Polyurethane In Artificial Leathermentioning
confidence: 99%
“…The whole glass was placed in the water bath at a constant speed and a fixed angle. According to some coagulation processes of WPL, 8,9,27,28 the process in this study is as follows: the film was first immersed in a water bath at 25 C for 10 minutes, then immersed in a water bath at 60 C for 30 min, and finally the washed film was dried at 80 C for 1 h to obtain WPL.…”
Section: Preparation Of Wet-type Polyurethane Leathermentioning
confidence: 99%
“…[5][6][7] Wet-type polyurethane artificial leather (WPL) is prepared by coating polyurethane solution (PUS) on non-woven, knitted fabric and other substrate, and then replacing organic solvents with water. 8,9 WPL is widely used in clothing, footwear, automobile decoration, office furniture and other fields. [10][11][12][13] PPCD synthesized from CO 2 and propylene oxide is a low molecular weight diol with the hydroxyl groups at the ends of its chains, which is one of the most widely used CO 2 -based oligomer.…”
Section: Introductionmentioning
confidence: 99%
“…The aging of MPFs will induce further fragmentation and subsequent formation of much smaller debris. Synthetic fabrics are always considered a major source of MPFs, among which polyester (PET) occupies the most global textile fibers market, given the production and consumption, contributing to MP pollution in the environment. , In addition to the exclusive application in apparel and home fabrics, the PET knitted fabric is also one of the common raw materials of polyurethane synthetic leather (PU leather) as the base cloth . PU synthetic leather has complex plastic compositions, including upper PU resin and PET base fabric, which could generate MP particles (MPPs, L/W ratio <3), MPFs, and even NPs simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…2,5 In addition to the exclusive application in apparel and home fabrics, the PET knitted fabric is also one of the common raw materials of polyurethane synthetic leather (PU leather) as the base cloth. 6 PU synthetic leather has complex plastic compositions, including upper PU resin and PET base fabric, which could generate MP particles (MPPs, L/ W ratio <3), MPFs, and even NPs simultaneously. Moreover, PET and PU are the main plastic polymers based on production volumes, which result in the small particles and fiber composition found in the environment.…”
Section: Introductionmentioning
confidence: 99%